(untitled) (ENTHYMEMA, 2022)
Presentazione della sezione “«We Should Never Write Without Feeling». Studi su William T. Vollmann”. Introduction to the monographic section “’We Should Never Write Without Feeling.’ Studies on William T. Vollmann”.